The Effect Of Inclusiveness And Diversity On The Performance Of Program Employees Through The Quick Reaction Team At The Social Office Jember District - Musyaffa Musyaffa; Nurul Qomariah; Ni Nyoman Putu Martini (UNIVED Press, 2025)
The role of human resources is becoming increasingly important as it relates to global developments that are full of competitive competition between large and small companies, both private and government companies. One of the ways that organizations can face competition is by empowering and exploring all the potential of their human resources to the fullest. This study aims to test and analyze the significant influence of employee inclusiveness and diversity on the Rapid Reaction Team (TRC) program and the performance of employees of the Jember Regency Social Service, This study uses a quantitative approach. The study population was 193 employees of the Jember Regency Social Service and the sample was taken using saturated sampling technique. The results showed that there was a significant influence of inclusiveness and diversity on the Rapid Response Team (TRC) Program. There is a significant influence of inclusiveness and diversity on employee performance. There is a significant influence of the Rapid Response Team (TRC) Program on employee performance. There is a significant influence of inclusiveness and diversity on employee performance through the Rapid Response Team (TRC) Program.